Progress in precision therapy in pediatric oncology. Issue 1 (13th February 2023) - O'Donohue, Tara; Farouk Sait, Sameer; Glade Bender, Julia
Abstract : Purpose of review: The fields of precision medicine and cancer genomics in pediatric oncology are rapidly evolving. Novel diagnostic tools are critical in refining cancer diagnoses, stratifying patient risk, and informing treatment decisions. This review is timely and relevant as it discusses advantages and drawbacks of common molecular profiling techniques and highlights novel platforms, which may address select limitations. We discuss recent publications demonstrating utility of large-scale molecular profiling and feasibility and logistics of matching targeted therapies to patients. Recent findings: We describe the increased accessibility of next-generation sequencing, complementary profiling methods, and strategies to guide treatment decisions. We describe curation and sharing of large genomic datasets and novel mechanisms to obtain matched targeted therapies. Importantly, we discuss relevant publications in distinct disease domains that support indications for evidence-based precision therapy. Lastly, we introduce the incremental analyses that can be obtained via whole-genome and transcriptome sequencing. Summary: Here we highlight high-yield clinical scenarios of precision medicine approaches and identify the ongoing challenges including universally defining clinical actionability, optimizing trial design to account for molecular heterogeneity while acknowledging limitations in patient accrual, expanding access to molecularly targeted therapies, and validating new tools and technology to aid in precision medicine therapeutic approaches.